(untitled) (The Research of Medical Science Review, 2025)
Background: Metabolic dysfunction associated fatty liver disease (MAFLD) and Non-alcoholic fatty liver disease (NAFLD/ non-MAFLD) are frequently associated with cardiovascular conditions, particularly acute coronary syndrome (ACS). These liver pathologies often coexist with traditional risk factors for coronary artery disease (CAD) and may exacerbate cardiovascular outcomes. Objectives: To determine the frequency of MAFLD and non- MAFLD among patients presenting with ACS and assess the relationship between the presence of fatty liver with associated comorbidities with the extent of CAD. Study Design & Setting: Cross-sectional analytical study conducted at the Department of Cardiology, Dr. Ruth KM Pfau Civil Hospital/ Dow University of Health Sciences, Karachi, from January 2024 to June 2024. Methodology: A total of 228 patients diagnosed with ACS were enrolled. All participants underwent abdominal ultrasonography for fatty liver and coronary angiography was done to assess CAD severity. Data on demographics, clinical history, biochemical parameters, and risk factors were collected and statistically analyzed using SPSS v25. Association between MAFLD and Non-MAFLD and CAD extent was evaluated using chi-square test and logistic regression. Results: MAFLD was present in 52.5% of ACS patients. A significant association was observed between MAFLD and multivessel CAD (p<0.001). MAFLD patients exhibited higher frequencies of hypertension (67.9%), diabetes (62.3%), and dyslipidemia (60.4%). MAFLD incidence positively correlated with CAD burden. Conclusion: MAFLD is highly prevalent in ACS patients and significantly correlates with the severity of coronary artery disease. Routine screening for FLD in ACS patients may aid in risk stratification and management.